Union of the Comoros : 2019 Article IV Consultation-Staff Report; Press Release. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
Economic developments over the past two years have been challenging due mainly to adverse impacts of political uncertainty (constitutional referendum in mid-2018 and elections in early 2019) and Cyclone Kenneth (April 2019), notwithstanding the provision of Fund emergency financial support following the cyclone.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet